Role and regulation of class-C flavodiiron proteins in photosynthetic organisms. Issue 17 (13th September 2019) - Alboresi, Alessandro; Storti, Mattia; Cendron, Laura; Morosinotto, Tomas
Abstract : The regulation of photosynthesis is crucial to efficiently support the assimilation of carbon dioxide and to prevent photodamage. One key regulatory mechanism is the pseudo-cyclic electron flow (PCEF) mediated by class-C flavodiiron proteins (FLVs). These enzymes use electrons coming from Photosystem I (PSI) to reduce oxygen to water, preventing over-reduction in the acceptor side of PSI. FLVs are widely distributed among organisms performing oxygenic photosynthesis and they have been shown to be fundamental in many different conditions such as fluctuating light, sulfur deprivation and plant submersion. Moreover, since FLVs reduce oxygen they can help controlling the redox status of the cell and maintaining the microoxic environment essential for processes such as nitrogen fixation in cyanobacteria. Despite these important roles identified in various species, the genes encoding for FLV proteins have been lost in angiosperms where their activity could have been at least partially compensated by a more efficient cyclic electron flow (CEF). The present work reviews the information emerged on FLV function, analyzing recent structural data that suggest FLV could be regulated through a conformational change.